2018
DOI: 10.1016/j.jpainsymman.2017.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Need and Availability in Four Referral Hospitals in Senegal: Results from a Multicomponent Assessment

Abstract: There is significant need for palliative care in Senegal. Training of health care workers and ensuring availability of relevant medications should be prioritized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Among the sample, participants' self-perceived knowledge and skills in providing palliative care/end-of-life care were low. Our findings support previous research showing that palliative care education among health and social care providers is often deficient in sub-Saharan Africa 27-29 . Although most participants reported that palliative care was provided to patients facing life-threatening illnesses, less than half had received training during their basic education, and even fewer had received training in the past 5 years.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Among the sample, participants' self-perceived knowledge and skills in providing palliative care/end-of-life care were low. Our findings support previous research showing that palliative care education among health and social care providers is often deficient in sub-Saharan Africa 27-29 . Although most participants reported that palliative care was provided to patients facing life-threatening illnesses, less than half had received training during their basic education, and even fewer had received training in the past 5 years.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings support previous research showing that palliative care education among health and social care providers is often deficient in sub-Saharan Africa. [27][28][29] Although most participants reported that palliative care was provided to patients facing life-threatening illnesses, less than half had received training during their basic education, and even fewer had received training in the past 5 years. The higher levels of self-perceived knowledge and skills among participants who received training in the past 5 years suggest that educational programs can improve these skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, estimates suggest that only 5% of people in Africa in need of palliative care are able to receive it ( Downing et al, 2015 ). Furthermore, past research on palliative care in Africa has often focused on countries with relatively well-developed programs such as Uganda, Kenya, and South Africa ( Downing et al, 2015 ; Drenth et al, 2017 ; Fraser et al, 2017 ; Grant et al, 2017 ), with less of a focus on West African, Francophone countries such as Senegal, where palliative care is less-developed ( Afolabi et al, 2021 ; Hamdi et al, 2017 ; Rhee, Garralda, Namisango, Luyirika, de Lima, Powell, Robinson, et al, 2018 ). Furthermore, scholars have noted gaps in research on palliative care in Sub-Saharan Africa ( Afolabi et al, 2021 ; Fraser et al, 2017 ; Hamdi et al, 2017 ; Harding & Higginson, 2005 ; Harding et al, 2013 ).…”
mentioning
confidence: 99%
“…Furthermore, past research on palliative care in Africa has often focused on countries with relatively well-developed programs such as Uganda, Kenya, and South Africa ( Downing et al, 2015 ; Drenth et al, 2017 ; Fraser et al, 2017 ; Grant et al, 2017 ), with less of a focus on West African, Francophone countries such as Senegal, where palliative care is less-developed ( Afolabi et al, 2021 ; Hamdi et al, 2017 ; Rhee, Garralda, Namisango, Luyirika, de Lima, Powell, Robinson, et al, 2018 ). Furthermore, scholars have noted gaps in research on palliative care in Sub-Saharan Africa ( Afolabi et al, 2021 ; Fraser et al, 2017 ; Hamdi et al, 2017 ; Harding & Higginson, 2005 ; Harding et al, 2013 ). In fact, Fraser and colleagues (2017) concluded in their review of palliative care in Uganda and Kenya that research is the most neglected area for informing clinical interventions, and a recent synthesis of current research evidence and gaps highlighted many information needs, most acute in northern and West Africa ( African Palliative Care Association [APCA], n.d.a ).…”
mentioning
confidence: 99%